Educational Communication in Learning Batik as Preservation of Local Wisdom Products for the Young Generation - Prasetiyo, Prasetiyo; Sulaiman, Adhi Iman; Prastyanti, Shinta (Technium Education and Humanities, 2022)
Batik as a product of artistic heritage, culture, local wisdom, and the identity of the Indonesian nation needs to be preserved, especially among the younger generation. The research aims to analyze This study aims to analyze the communication of batik education for the younger generation as an effort to preserve local wisdom products. The research used case studies to be able to construct reality more deeply by collecting data through observation, in-depth interviews, documentation, and Focus Group Discussions (FGD) as well as using qualitative analysis. Research informants were determined through purposive sampling consisting of teachers and students in grades XI and XII who entered the batik department at the research location of the Vocational High School in the Susukan area and the Wardah batik business group as partners in internship and practicum activities as research locations in Susukan District. Banjarnegara Regency, Central Java Province of Indonesia. The results showed: (1) Batik craftsmen and entrepreneurs have generally from the old age group above 50 years old and only become part-time or additional workers, so there is a need for regeneration of batik among the younger generation. (2) Students choosing batik majors have the potential to become the next generation to become batik craftsmen and entrepreneurs. (3) Batik needs to be preserved, especially among the younger generation with the support of government policies through formal educational communication in the curriculum of the school and non-formal materials with continuous community empowerment, then requiring the use of batik products for school uniforms and public or private employees. (4) The subject matter and batik empowerment program are designing batik motifs, making batik to coloring with textile chemicals and natural dyes, making eco-prints, and marketing promotion media for batik products.